133k views
2 votes
Solve the formula Ax + By = C for x.A. X= C+ByAB. X= C-C. x = CFR+C-ByD. X=+ By

Solve the formula Ax + By = C for x.A. X= C+ByAB. X= C-C. x = CFR+C-ByD. X=+ By-example-1
User Hiren
by
5.6k points

1 Answer

5 votes

Step 1:

Write the equation


Ax\text{ + By = C}

Step 2:

To make x subject of the relation, you will need to solve for x.


\begin{gathered} Ax\text{ + By = C} \\ Ax\text{ = C - By} \\ \text{Divide through by A} \\ (Ax)/(A)\text{ = }\frac{\text{C - By}}{A} \\ \text{x = }\frac{\text{C - By}}{A} \end{gathered}

Final answer


\begin{gathered} \text{x = }\frac{\text{C - By}}{A} \\ \text{Option C} \end{gathered}

User Roman Pfneudl
by
5.3k points